ScRNA-Seq and imaging mass cytometry analyses unveil iNKT cells-mediated anti-tumor immunity in pancreatic cancer liver metastasis. (1st May 2023) - Yi, Qijun; Wang, Jie; Liu, Tingting; Yao, Yi; Loveless, Ian; Subedi, Kalpana; Toor, Jugmohit; Adrianto, Indra; Xiao, Hua; Chen, Bin; Crawford, Howard C.; Fang, Deyu; et al.
Abstract: Invariant natural killer T (iNKT) cells are innate-like T cells that are abundant in liver sinusoids and play a critical role in tumor immunity. However, the role of iNKT cells in pancreatic cancer liver metastasis (PCLM) has not been fully explored. In this study, we employed a hemi-spleen pancreatic tumor cell injection mouse model of PCLM, a model that closely mimics clinical conditions in humans, to explore the role of iNKT cells in PCLM. Activation of iNKT cells with α-galactosylceramide (αGC) markedly increased immune cell infiltration and suppressed PCLM progression. Via single cell RNA sequencing (scRNA-seq) we profiled over 30, 000 immune cells from normal liver and PCLM with or without αGC treatment and were able to characterize the global changes of the immune cells in the tumor microenvironment upon αGC treatment, identifying a total of 12 subpopulations. Upon treatment with αGC, scRNA-Seq and flow cytometry analyses revealed increased cytotoxic activity of iNKT/NK cells and skewing CD4 T cells towards a cytotoxic Th1 profile and CD8 T cells towards a cytotoxic profile, characterized by higher proliferation and reduced exhaustion marker PD1 expression. Moreover, αGC treatment excluded tumor associated macrophages. Lastly, imaging mass cytometry analysis uncovered the reduced epithelial to mesenchymal transition related markers and increased active CD4 and CD8 T cells in PCLM with αGC treatment. Overall, our findings uncover the protective function of activated iNKT cells in pancreatic cancer liver metastasis through increased NK and T cell immunity and decreased tumor associated macrophages. Graphical abstract: Image 1 Highlights: Mapped and characterized global immune cell changes in Pancreatic Cancer Liver Metastasis (PCLM) after αGC treatment. Enhanced cytotoxic activity of iNKT/NK cells after αGC treatment in PCLM. CD4 T cells shifted to Th1 profile with enhanced cytotoxicity after αGC treatment in PCLM. CD8 T cells skewed with high proliferation and low exhaustion after αGC treatment in PCLM. Additionally, αGC treatment excluded tumor associated macrophages in PCLM.